2022
DOI: 10.1111/mec.16552
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition does not associate with toxoplasma infection in rats

Abstract: Toxoplasma infection in intermediate host species closely associates with inflammation. This association has led to suggestions that the behavioural changes associated with infection may be indirectly driven by the resulting sustained inflammation rather than a direct behavioural manipulation by the parasite. If this is correct, sustained inflammation in chronically infected rodents should present as widespread differences in the gastrointestinal microbiota due to the dependency between the composition of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…Our results were in contrast with the findings by Taggart et al (2022), who reported that the chronic infection of T. gondii did not change the gut microbiota structure of Wistar Hannover rats and concluded that chronical infection may not cause persistent inflammation in rats. The differences for these results may be due to a variety of experimental designs.…”
Section: The Genus-level Resolution Revealed the Effect Of T Gondii I...contrasting
confidence: 99%
“…Our results were in contrast with the findings by Taggart et al (2022), who reported that the chronic infection of T. gondii did not change the gut microbiota structure of Wistar Hannover rats and concluded that chronical infection may not cause persistent inflammation in rats. The differences for these results may be due to a variety of experimental designs.…”
Section: The Genus-level Resolution Revealed the Effect Of T Gondii I...contrasting
confidence: 99%
“…Although not an exact proxy, the fecal microbiome reflects the trillions of microbes that reside in the gastrointestinal tract; microbes that collectively contribute to host digestion, immunity and pathogen defense, and intestinal barrier homeostasis [ 1 ]. While the composition of the fecal microbiome is highly dynamic and can correlate with a range of host factors including age [ 2 , 3 ], sex [ 4 ], body condition [ 5 ], diet [ 6 , 7 ], and antibiotic use [ 8 ], more persistent changes in composition have also been associated with disease and infections [ 9 , 10 ]. Compared to their healthy counterparts, the fecal microbiome of animals with a disease or infection may have reduced microbial diversity [ 11 ], decreased abundances of functionally important microbes like fermentative or short-chain fatty acid (SCFA)-producing bacteria [ 12 ], or elevated abundances of pathogenic taxa [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%